Id2 protein expression in malignant ovarian tumours - Czekierdowska, Sylwia; Czekierdowski, Artur; Kotarski, Jan (Menopause Review/Przegląd Menopauzalny, 2009)
It has been suggested that various proteins from the “Id” group may play an important role in malignant tumour angiogenesis and metastasis formation. Our aim was to assess whether the expression of Id2 proteins is associated with tumour type, histological grading and FIGO stage in women with malignant ovarian neoplasms. The mean age of 49 patients operated on was 56.1 ±12.7 years (range: 27-80 years) and 18 (36.7%) women in this group were pre-menopausal. Histological examination revealed that more than half of tumours were serous ovarian cancers (n = 26). Other malignancies included 14 mucinous, 5 endometrioid and 4 metastatic tumours. Expression of Id2 protein estimated semiquantitatively (as 1 to 9 points) was found in 40 cases. In 40% of these tumours (n = 17) a high degree of Id2 expression was found. All 9 (19%) tumours without expression of Id2 were serous ovarian cancers. Id2 protein was found in both nuclei and cytoplasm of cancer cells. Also some staining was seen in pericytes adjacent to the microcapillary lumen. In 19 of 25 cases (76%) of low FIGO stage (I and II) tumours Id2 expression was medium or high. Histological grading also had a significant influence (p = 0.009) on Id expression. Most (12 of 18) low-grade tumours (G3) had medium or high Id2 content assessed as 5 to 9 points. Menopausal status had no significant influence on intensity of Id2 staining. High expression of Id2 protein (7 to 9 points) was observed in women before (39%) and after menopause (32%). However, absent Id2 expression was predominantly found in women after menopause (8 of 9 cases). Based on these preliminary results we conclude that the assessment of Id2 protein may be used as an additional parameter to characterize various types of malignant tumours in women.